Os recursos minerais do Município de Caracaraí - RR - Silva, Laudimira Luso da (2011)
The minerals are present in everyday human under the most varied forms, whether in the field of metallurgy, chemical industry, construction or farming. In general, it appears that the path followed by the development of humanity was and is achieved by seeking and use of mineral commodities. Given the territorial extension and geological diversity found in soil and subsoil, Brazil has great potential as a holder of mining on the world stage. In this context, Roraima is in a region that has traditionally focused on the exploitation of minerals, especially gold and diamonds. Main river port in the state of Roraima, very important in the recent past, the city of Caracaraí - RR lost its axial with the construction of highway BR-174. The development of their rural area is based on farming, the urban core in trade and services and the mining industry still in its infancy. This study focuses on a survey of economically important mineral resources, including those in the exploration stage in the city, using as auxiliary products of remote sensing and field data. We surveyed 19 sampling points, eight near the BR-174 and 11 in bibliography. Images were prepared letters of mineral occurrences, mineral and mining activity. Caracaraí has areas of mineral potential, such as sand, gravel, clay, granite and laterite, with gold occurrences. Other minerals have been discovered in the form of small deposits still poorly investigated, but the areas allocated to indigenous lands and conservation, leading to reduce the exploitation of them and create barriers impeding progress in geological knowledge and discoveries of new mineral occurrences in the city.